2016
DOI: 10.3906/sag-1409-79
|View full text |Cite
|
Sign up to set email alerts
|

Serological prevalence of human parvovirus B19 in diseases or disordersrelated to different human body systems

Abstract: IntroductionHuman parvovirus B19 (B19), frequently seen all over the world, is a pathogenic agent associated with various diseases and disorders that affect different body systems. Erythema infectiosum, chronic arthritis, spontaneous abortion, hematological disorders, myocarditis, and glomerulonephritis are only some of these (1-3). B19 is spread from person to person by infected respiratory secretions, by infected blood and blood-product transfusions, and by vertical transmission from mother to fetus (4,5).B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
5
0
3
Order By: Relevance
“…[27] In Erzurum, Aktas et al found in the general population that parvovirus IgG was 27.8%, IgM was 8.5% and IgM and IgG seropositivity together was 2.5%. [28] In Ankara, Goral et al found in blood donors that parvovirus B19 IgG seropositivity was 58.9% and IgM seropositivity was 3.92%. [29] In this study, parvovirus B19 IgG positivity was 66% and IgM positivity was 3% in patients with prediagnosis of arthritis/arthralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] In Erzurum, Aktas et al found in the general population that parvovirus IgG was 27.8%, IgM was 8.5% and IgM and IgG seropositivity together was 2.5%. [28] In Ankara, Goral et al found in blood donors that parvovirus B19 IgG seropositivity was 58.9% and IgM seropositivity was 3.92%. [29] In this study, parvovirus B19 IgG positivity was 66% and IgM positivity was 3% in patients with prediagnosis of arthritis/arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Low rates of IgM seropositivity were consistent with the ones in other similar studies. [28,29] Parvovirus B19 IgM prevalence in the general population is generally under 2%. However, the rate may be higher, depending on the duration of the outbreak cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Parvovirus B19 özgül Ig M antikorları virüse maruz kalınmasından yaklaşık 10 gün sonra ortaya çıkar ve 3-6 ay kalabilir, Ig G antikorları ise yaklaşık 2 hafta sonra ortaya çıkar ve ömür boyu kalır. Bu antikorların prevalansı bölgeden bölgeye değişebilir [12].…”
Section: ö Z E Tunclassified
“…Ülkemizden konuyla ilgili farklı hasta grupları ve farklı yaş gruplarını içeren çalışmalar bulunmaktadır. Ülkemiz çalışmalarına bakıldığında farklı hasta ve yaş grubundaki çalışmalardaki oranlar %16-64 arasında değiştiği görülmektedir [2,[11][12][13][14][15]. Parvovirus B19 prevalansı ile ilgili ülkemizden farklı hasta grupları ile yapılmış çalışmaların sonuçları Tablo 2' de yer almaktadır.…”
Section: ö Z E Tunclassified
See 1 more Smart Citation